Polyautoimmunity Reflecting Immune Dysregulation in Common Variable Immunodeficiency - Maria Giovanna Danieli; Giuseppe Murdaca; Cristina Mezzanotte; Ilaria Claudi; Elena Buti; Matteo Martini; Maria Beatrice Bilò; Sebastiano Gangemi; Gianluca Moroncini (Biomedicines)
Background: Common variable immunodeficiency (CVID) is the most frequent symptomatic inborn error of immunity (IEI) in adulthood. Other than recurrent infections, CVID may present with non-infectious complications such as enteropathy, lymphoproliferation, malignancy, and autoimmune diseases. Patients could have a single autoimmune disease (monoautoimmunity) or two or more autoimmune diseases (overt polyautoimmunity). “Latent polyautoimmunity” corresponds to the presence of autoantibodies without a clinically evident autoimmune disease. Methods: The aim of this retrospective study was to describe autoimmunity and polyautoimmunity in a population of 81 CVID adult patients, enrolled from January 2008 to July 2022 (mean follow-up: 8.5 years). Results: We documented at least one autoimmune disorder in 40 patients (49.4%). Moreover, 15 subjects (37.5% of patients with autoimmunity and 18.5% of all CVID population) presented polyautoimmunity. Despite the humoral immune deficiency, we detected different autoantibodies in CVID patients with or without a concomitant autoimmune disease. In both groups with monoautoimmunity and polyautoimmunity, cytopenias were the most common manifestation. Conversely, enteropathy was recorded only in patients with polyautoimmunity (27%, p = 0.006). Patients with polyautoimmunity showed a significantly lower mean age at diagnosis (−12 years, p = 0.018) compared to those with monoautoimmunity. We documented a higher frequency of autoimmunity in CVID patients who had increased diagnostic (+5.6 years) and therapeutic (+7.2 years) delay (p = 0.093 and 0.054, respectively). Conclusions: Polyautoimmunity is a frequent condition in patients affected by CVID. An early start of Ig replacement therapy could help prevent autoimmune complications.